1999
DOI: 10.1046/j.1365-2648.1999.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐registration diploma students: a quantitative study of entry characteristics and course outcomes

Abstract: Nurse education has been transformed over the last decade and continuing change is likely. Nurse educators are responsible for meeting the quality assurance standards of local stakeholders and student retention and progress are important aspects of this process. As part of a monitoring exercise, an enquiry was set up to review pre-registration selection and recruitment strategies and to establish if there were any significant relationships between the characteristics of pre-registration diploma entrants and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 44 publications
6
63
0
5
Order By: Relevance
“…31 Also, in case of a highly feminised profession such as nursing, it was observed that men bear a sig nificantly higher risk of dropping out than women. 13,[32][33][34] On the other hand, studies performed among the participants of a military medical programme show that it is women who present a greater attrition risk than men (OR=2.4). Also, when learning at a dental school, a tendency is observed among men to achieve higher scores in the practical tests and better grade averages, however, there is no data on the subject of risk evalua tion in this field of studies.…”
Section: Discussionmentioning
confidence: 99%
“…31 Also, in case of a highly feminised profession such as nursing, it was observed that men bear a sig nificantly higher risk of dropping out than women. 13,[32][33][34] On the other hand, studies performed among the participants of a military medical programme show that it is women who present a greater attrition risk than men (OR=2.4). Also, when learning at a dental school, a tendency is observed among men to achieve higher scores in the practical tests and better grade averages, however, there is no data on the subject of risk evalua tion in this field of studies.…”
Section: Discussionmentioning
confidence: 99%
“…À notre connaissance, il s'agit de la seule étude antérieure qui a vérifié ce lien. Par ailleurs, les résultats obtenus de la présente étude permettent de clarifier ceux des études antérieures selon lesquelles plus les étudiants sont âgés, meilleure est leur performance académique (El Ansari, 2002 ;Kevern et al, 1999;McKenzie & Schwitzer, 2001;Sheard, 2009). Cette relation est donc valable lorsque la performance académique est mesurée par les scores au test à choix multiples.…”
Section: Les Variables Contrôleunclassified
“…Elle se différencie sur au moins un aspect important: elle utilise les scores réellement obtenus à ces méthodes d'évaluation plutôt que des scores auto-rapportés. Afin de quantifier l'impact réel de la personnalité, cette étude contrôlera pour le genre et l'âge car ces variables semblent influencer tant la personnalité (Budaev, 1999;Dollinger & Orf, 1991;Donnellan & Lucas, 2008;Furnham, Chamorro-Premuzic, & McDougall, 2003;Lakhal et al, 2015;Rubinstein, 2005;Schmitt, Realo, Voracek, & Allik, 2008) que la performance académique (El Ansari, 2002;Kevern, Ricketts, & Webbs, 1999;McKenzie & Schweitzer, 2001;Sheard, 2009 & Furnham, 2005). Le trait varie en degré d'un individu à l'autre et les sujets peuvent être classifiés en fonction du degré qu'ils possèdent de chacun de ces traits (McCrea & Costa, 1990).…”
unclassified
See 1 more Smart Citation
“…Another important concept to consider when measuring degree courses' quality is the dropout prevention, the students abandoning the courses are usually those who had low grades in pre-entrance tests (Houltram, 1996;Kevern et al, 1999;Pryjmachuk et al, 2009), with parents who did not graduate, with a lower socioeconomic status; other important factors are student's age (Houltram, 1996;Kevern et al, 1999;Mulholland et al, 2008;Pryjmachuk et al, 2009), gender (Mulholland et al, 2008;Pryjmachuk et al, 2009) and course's topic (Higher Education Funding Council England, 2000;McMillan, 2005;Jeffreys, 2007). However, just one factor can be sufficient to cause drop out.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%